An analysis of fracture toughness, at third mode fracture in concretes containing fly-ash additives - Golewski, Grzegorz (Budownictwo i Architektura / Civil and Architectural Engineering, 2013)
This paper presents the results of fracture toughness tests of concrete with fly ash (FA), specified at the third model fracture. Concrete composites with the additives of 0%, 20% and 30% siliceous FA were analysed. Fracture toughness tests were performed on axial torsion machine MTS 809 Axial/Torsional Test System, using the cylindrical specimens with dimensions of 150/300 mm, with a circumferential notch made in the half-height of cylinders. The studies examined effect of FA additive on the parameter KIIIc. The Analysis of the results revealed that a 20% FA additive causes increase in KIIIc, while a 30% FA additive causes decrease in fracture toughness.